Fruit-Carrot-Based Smoothies as Innovative Products with a Complex Matrix of Bioactive Compounds Effected on Activities of Selected Digestive Enzymes and Cholinesterases In Vitro - Emel Hasan Yusuf; Aneta Wojdyło; Ana Isabel Bourbon; Paulina Nowicka (MDPI AG, 2023)
In this study, four different carrot varieties (purple, yellow, white, and orange) were used in the production of smoothies with raspberry, apple, pear, strawberry, and sour cherry juices. The in vitro inhibition effects against α- amylase, α- glucosidase, pancreatic lipase, acetylcholinesterase, and butyrylcholinesterase were measured, bioactive compounds, physicochemical characteristics, including sensorial features were described. The antioxidant activities of the studied samples were analyzed using the ORAC, ABTS, and FRAP methods. The raspberry-purple carrot smoothie showed the highest antioxidant activity against lipase and butyrylcholinesterase enzyme activity. The sour cherry-purple carrot smoothie showed the highest total soluble solids, total phenolic acid, total anthocyanins, and procyanidin contents; dry mass; and osmolality. Although the apple-white carrot smoothie achieved the highest acceptance after sensorial evaluation, it did not exhibit any potent biological activities. Thus, food products with purple carrot, raspberry, and sour cherry ingredients are suggested as functional and/or novel matrix compositions with high antioxidant potential.